Analysis of The Antibiotic Resistance Problem - M. A. Maistrenko; E. N. Yakusheva; D. S. Titov (Антибиотики и Химиотерапия, 2023)
Antibiotic resistance is a global health problem. Its solution requires concerted efforts on the scale of global cooperation. Programs to prevent the development of antibiotic resistance, as well as to stimulate the development of new drugs with antimicrobial activity are implemented in a lot of countries. The use of antibacterial drugs, including inappropriate use, has increased during the COVID-19 pandemic, which may contribute to the growth of antibiotic resistance. The aim of this study is to assess the measures aimed at combating the growing antibiotic resistance in the world, analyze the market of antimicrobial drugs in the Russian Federation, as well as collect and process information on the antibiotic resistance of microorganisms that cause infectious diseases that develop against the backdrop of COVID-19. The analysis of the state register of the Russian Federation for antibacterial drugs was carried out. Mathematical and statistical processing of antibiotic resistance was performed according to the data of the European Surveillance Atlas of Infectious Diseases for Klebsiella pneumonia in relation to fluoroquinolones, aminoglycosides, third-generation cephalosporins, as well as combined resistance to these antibacterial drugs over the past sixteen years.